Reseаrching pedestriаn movement in city streets (Международный научный журнал «Инженер», 2026)
The article carefully analyzes the need for the study of pedestrian behaviour in the city streets, its determinants, and the methods of research. One of the major goals of planning within the city has been the improvement of pedestrian flows as well as the need to guarantee safety. A set of measures such as determining the parameters of pedestrian movement, obtaining data and applying statistical processes to it, and constructing movement models using new technologies were determined to be necessary. Thorough planning for urban structure provides opportunities for improvement of flows of pedestrian in the cities. The quality of urban infrastructure, the presence of safe sidewalks, crossing places, traffic lights, and other convenience features influence directly the effectiveness and safety of movement of pedestrians.The research specifically focused on the necessity to factor the requirements of pedestrians under the design of the resultant infrastructure and the plans which endeavours to aid their mobility. It has also been noted the significance of studying pedestrian movements, analysing how this enables the recognition of activity patterns on streets, pedestrian traffic, and diagnosing certain issues. The analysis results support recommendations that seek to enhance urban infrastructure, pedestrian welfare, and urban mobility control. Moreover, the article gave comprehensive description about modeling techniques. It has extensively discussed the simulation of pedestrian activities in computer programs through modern technologies, predicting movement congestion for different scenarios, and evaluating the effectiveness of infrastructure. It was proposed that this modeling technique can be useful in the management of urban development and infrastructure planning because its outputs are useful in formulating different movement control strategies.